On the role of environmental corruption in healthcare infrastructures: An empirical assessment for Italy using DEA with truncated regression approach. Issue 5 (May 2017) - Cavalieri, Marina; Guccio, Calogero; Rizzo, Ilde
Highlights: We investigate the role of environmental corruption in provision of healthcare infrastructures. We focus on Italy as a case study, employing a dataset of contracts for healthcare infrastructures. We perform our empirical assessment employing a bootstrap truncated two-stage DEA approach. We find that the performance of the contracts is significantly affected by corruption. Healthcare contracting authorities are both less efficient and more at risk of corruption that other procures. Abstract: Objectives: This paper investigates empirically whether the institutional features of the contracting authority as well as the level of 'environmental' corruption in the area where the work is localised affect the efficient execution of public contracts for healthcare infrastructures. Methods: A two-stage Data Envelopment Analysis (DEA) is carried out based on a sample of Italian public contracts for healthcare infrastructures during the period 2000–2005. First, a smoothed bootstrapped DEA estimator is used to assess the relative efficiency in the implementation of each single infrastructure contract. Second, the determinants of the efficiency scores variability are considered, paying special attention to the effect exerted by 'environmental' corruption on different types of contracting authorities. Results: Our results show that the performance of the contracts for healthcare infrastructures is significantly affected by 'environmental' corruption. Furthermore, healthcare contracting authorities are, on average, less efficient and the negative effect of corruption on efficiency is greater for this type of public procurers. Conclusions: The policy recommendation coming out of the study is to rely on 'qualified' contracting authorities since not all the public bodies have the necessary expertise to carry on public contracts for healthcare infrastructures efficiently.